2018
DOI: 10.3390/ijerph15071356
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Outdoor Play of Children in Public Playgrounds—Do Gender and Social Environment Matter?

Abstract: Background: Few studies have delved into the relationship of the social environment with children’s physical activity and outdoor play in public playgrounds by considering gender differences. The aim of the present study was to examine gender differences and the relationship of the social environment with children’s physical activity and outdoor play in public playgrounds. Methods: A quantitative, observational study was conducted at ten playgrounds in one district of a middle-sized town in Germany. The social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 54 publications
1
40
2
5
Order By: Relevance
“…Sports segregation according to gender roles may be related to the fear of being judged or bullied if gender norms are not conformed to [37,48]. In fact, various articles have shown that girls are more likely to engage in team sports when other girls are playing but not when boys are playing, because boys may exclude girls when they try to participate in sports in which girls are not socially considered good enough [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Sports segregation according to gender roles may be related to the fear of being judged or bullied if gender norms are not conformed to [37,48]. In fact, various articles have shown that girls are more likely to engage in team sports when other girls are playing but not when boys are playing, because boys may exclude girls when they try to participate in sports in which girls are not socially considered good enough [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effect of two independent variables from the game were studied: the score and the subroles associated with the Hunter and Hare roles on the dependent variables represented by Marro360 • strategic chains. Each of these chains was simultaneously integrated by the type of response according to the decision risk (risk in the decision), the relationship, and the energy intensity (Reimers et al, 2018). It is unavoidable to mention that the methodological approach used by the present study became feasible, since the integration of different variables (dynamic score, role, subrole, relation, decision risk, energy) was addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The higher level of total PA in boys could be explained by a higher intrinsic motivation and experiencing more pleasure from exercise compared to girls (31). Furthermore, previous studies found gender differences concerning different PA types (32,33). The results of the study of Reimers et al (2018) showed that boys were more likely to engage in sports and active games, while girls prefer walking and/running or to play in a playground (33).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, previous studies found gender differences concerning different PA types (32,33). The results of the study of Reimers et al (2018) showed that boys were more likely to engage in sports and active games, while girls prefer walking and/running or to play in a playground (33). It is recommended to provide tailored PA types in order to stimulate and improve PA. Additionally, the negative association between PA and age highlights the importance of early PA promotion since the presence of comorbidities is already evident in primary school children with obesity (34).…”
Section: Discussionmentioning
confidence: 95%